아동소비자의 자기조절능력, 물질주의 및 이타주의가 윤리적 소비행동에 미치는 영향 - 복미정(Mi-Jung Bok); 서정희(Jeong-Hee Seo) (한국컴퓨터정보학회논문지, 2018)
This purpose of this study was to analyze the variables associated with the ethical consumption behavior of children consumers. This subjects were 431 elementary school students. PASW 18.0 was used for data processing to do frequency analysis, T-test, one-way ANOVA, correlation analysis and multiple regression analysis. The results were as follows. First, children consumers tend to a little higher everyday ethical consumption behavior than others-oriented ethical consumption behavior. Second, as a result of analyzing ethical consumption behavior according to social economic variables, a high tendency of ethical consumption behavior was shown in groups that personality is extrovert and their household economic status is over upper middle class and father’s age is higher. Third, the variables affecting ethical consumption behavior of children consumers were self-regulation ability, materialism, altruism, personality tendency, household economic status. Materialism had a negative effect but self-regulation ability, materialism, altruism, personality tendency, and household economic status had a positive effect. KCI Citation Count: 0